KONSTRUKSI SOSIAL TENTANG PERATURAN DESA DALAM UPAYA PENANGGULANGAN POLUSI UDARA - Jayamagasta, Yua Gama (Paradigma, 2021)
Abstract This research is motivated by air pollution that continues to occur in Tropodo Village, Krian. Village regulations on air pollution control that have been set are not running optimally. Village regulations concerning air pollution countermeasures that have not been implemented optimally. The purpose of this study was to identify the efforts of the village government in controlling the implementation of village regulations, the objective conditions of the community, the triggers behind the dysfunction of village regulations, and analyze the social construction of tofu factory owners and the community regarding village regulations governing air pollution prevention. This research method uses a qualitative method with a case study approach and is studied using the social construction theory of Peter L. Berger. Data obtained by means of observation, interviews, documentation and audiovisual. The results showed the externalization process by planting the use of plastic 2 waste as fuel from the previous tofu factory owners. The objectivation process is demonstrated by understanding the characteristics of plastic waste which tend to have a positive impact on the Tropodo economic sector. The internalization process is indicated by the emergence of public awareness about meeting the needs of the economic sector which is far more important than the health sector. Through this social construction, it can be seen that Village Regulation No.06/2014 has not been obeyed by the community, air pollution is still an unresolved problem, and people with ARI in nearby health facilities are dominated by the Tropodo community. Keywords: Air Pollution, Village Regulations, Plastic Waste